2016
DOI: 10.1002/1873-3468.12483
|View full text |Cite
|
Sign up to set email alerts
|

Centromere protein W interacts with beta‐transducin repeat‐containing protein 1 and modulates its subcellular localization

Abstract: Beta-transducin repeat-containing protein 1 (b-TrCP1) is a substrate-recognition module of SCF b-TrCP1 ubiquitin ligases and its subcellular distribution is known to be critical for target specificity. Heterogeneous nuclear ribonucleoprotein (hnRNP) U, an abundant nuclear protein, is known to be a unique regulator of b-TrCP1 shuttling between the cytoplasm and the nucleus. In this study, we report that centromere protein W (CENP-W), which is frequently overexpressed in a variety of human cancers, may also cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…We identified that CSN-5 interacts with CENP-W and modulates CENP-W protein stability (10). Another of our studies revealed that CENP-W binds with b-TrCP-1 and contributes its nucleocytoplasmic shuttling (11), which raises the possibility that CENP-W is functionally related to the SCF b-TrCP-1 complex. In the current study, we provide evidence that CENP-W associates with SCF b-TrCP-1 components by replacing SKP-1 and inhibiting its ubiquitin ligase activity, suggesting that CENP-W is a new regulator that contributes to the fine tuning of SCF b-TrCP-1 E3 ligase activity.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…We identified that CSN-5 interacts with CENP-W and modulates CENP-W protein stability (10). Another of our studies revealed that CENP-W binds with b-TrCP-1 and contributes its nucleocytoplasmic shuttling (11), which raises the possibility that CENP-W is functionally related to the SCF b-TrCP-1 complex. In the current study, we provide evidence that CENP-W associates with SCF b-TrCP-1 components by replacing SKP-1 and inhibiting its ubiquitin ligase activity, suggesting that CENP-W is a new regulator that contributes to the fine tuning of SCF b-TrCP-1 E3 ligase activity.…”
mentioning
confidence: 71%
“…Our prior study revealed that CENP-W interacts with b-TrCP1 and contributes to its nuclear translocation (11). To clarify the specificity of this interaction, we performed a binding assay with other F-box family proteins.…”
Section: Cenp-w Associates With B-trcp1 By Replacing Skp1mentioning
confidence: 99%
“…It has been shown that hnRNP‐U, HIV‐1 Vpu, and TRIM9 compete with β‐TrCP1 for substrates binding, thereby limiting the β‐TrCP1 E3 ligase activity [41–43]. Further, it has been reported that centromere protein CENP‐W regulates shuttling of β‐TrCP1 between the cytoplasm and the nucleus [44]. CENP‐W also destabilizes β‐TrCP1 E3 ligase complex resulting in degradation [45].…”
Section: Discussionmentioning
confidence: 99%
“…Centromere protein W (CENP-W) and heterogeneous nuclear ribonucleoprotein U (hnRNP U) interact with the region of F box and the WD40 domain of β-TrCP1, respectively [122]. The interaction complex leads to a stable shuttling complex, resulting in the accumulation of β-TrCP1 in the nucleus and promoting cell migration.…”
Section: Regulation Of β-Trcp Activity 61 Upstream Effectors Of β-Trc...mentioning
confidence: 99%
“…The interaction complex leads to a stable shuttling complex, resulting in the accumulation of β-TrCP1 in the nucleus and promoting cell migration. It has been proposed that CENP-W may enhance the oncogenic potential of β-TrCP1 by promoting its nuclear accumulation [122].…”
Section: Regulation Of β-Trcp Activity 61 Upstream Effectors Of β-Trc...mentioning
confidence: 99%